Peran E-Trust dalam Memediasi Pengaruh E-Service Quality dan Promosi terhadap Keputusan Pembelian: (Studi pada Konsumen Shopeefood Denpasar) - Ni Putu Ayu Mirah Cahyani Putri; I Gusti Ayu Tirtayani (Journal of Management and Creative Business, 2026)
The rapid growth of app-based food delivery services has intensified competition among digital platforms, making e-service quality, promotional activities, and consumer trust important determinants of purchase decisions. This study examines the effects of E-Service Quality and Promotion on Purchase Decision, with E-Trust serving as a mediating variable among ShopeeFood users in Denpasar City. A quantitative approach was employed involving 200 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results demonstrate that E-Service Quality and Promotion have positive and significant effects on both Purchase Decision and E-Trust. Furthermore, E-Trust positively and significantly influences Purchase Decision and partially mediates the relationships between E-Service Quality and Purchase Decision, as well as between Promotion and Purchase Decision. These findings highlight that improving electronic service quality and implementing effective promotional strategies, supported by stronger consumer trust, can enhance customers’ purchase decisions. The study provides practical insights for ShopeeFood in developing customer-oriented service and promotional strategies to strengthen consumer trust and encourage purchase decisions.